(untitled) (Al-Qamar, 2022)
Faiz Ahmad Faiz was a very well known and trendsetter poet of Urdu literature. He has been recognized as the most important poet of Urdu poetry after Allama Muhammad Iqbal. He influenced his contemporaries as well as an entire subsequent generation with his elegant and refreshing poetic tone. The best artistic and poetic qualities are found in his style. His major achievement is that he invented a new diction and presented the best combination of romance and revolution. Among his main poetic themes or topics are laborers and farmers, poverty and economic exploitation, oppression and social injustice, resistance against didtatorship, world peace and the problems of the suffering humanity of the whole world and their solutions.